PENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA MELALUI MODEL BELAJAR KOOPERATIF TIPE TIME GAMES TOURNAMENT (TGT) PADA SISWA KELAS XII JASA BOGA 3 SMK N 6 PADANG - Atini, Sri (TINGKAP, 2016)
ABSTRACTThis article discusses the results of a classroom action research on enhancing the mathematical learning activity and learning achievements through the implementation of cooperative learning model of Time Games Tournament (TGT) in Class XII3 Hospitality at SMKN 6 Padang. This action research was conducted in two cycles, the first cycle was held on January 4, 2016 until January 20, 2016, and the second cycle conducted on January 25, 2016 until February 9, 2016. The finding of this research indicated that the implementation of cooperative learning model Time Games Tournament (TGT) was quite effective in enhancing the student activity and learning achievements of mathematics in class XII3 Hospitality at SMKN 6 Padang. The mastery of the subject matter has exceeded the specified Minimal Completeness Criteria (KKM), that is 70. Based on this study, it can be concluded that the activity and learning achievements of math students of class XII3 Hospitality at SMKN 6 Padang can be improved with the implementation cooperative learning model of team games tournament. Keywords: Learning activities, learning achievement, cooperative learning, Games Tournament (TGT)